Between Realpolitik And Islamic Solidarity: A Critical Evaluation Of Indonesia's Foreign Policy On The Gaza Conflict Under President Prabowo Subianto - Muhamad Barqi Asila (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2026)
Indonesia's foreign policy towards the Gaza conflict under President Prabowo Subianto has sparked intense public debate regarding the nation's moral positioning in international relations. While Indonesia consistently voices support for Palestinian independence through diplomatic channels and humanitarian aid, its participation in multilateral "peace" forums initiated by the United States and its allies is perceived by some observers as a pragmatic compromise that potentially undermines principled solidarity. This article critically evaluates these policies through an integrated analytical framework comprising three perspectives: (1) Islamic political ethics, (2) contemporary scholarly ijtihad, and (3) international political analysis. Employing a qualitative method with Critical Discourse Analysis (CDA), this study examines official government statements (2023-2024), ulama fatwas from major Indonesian Islamic organizations (MUI, NU, Muhammadiyah), and literature on Islamic political ethics. The findings reveal a fundamental tension between the principle of Muslim solidarity (ukhuwah islamiyah) and the demands of realpolitik in contemporary diplomacy. While Islamic ethics emphasize justice ('adl), public interest (maslahah), and trustworthiness (amanah) as normative parameters, political analysis highlights the structural dilemma between moral idealism and national strategic interests. Specifically, this study identifies three key issues: (1) the ambiguity between rhetorical support and concrete diplomatic action, (2) the divergence between Islamic organizational positions and government policy, and (3) the risk of credibility erosion in Indonesia's soft power as a Muslim-majority mediator. This study concludes that Indonesia's foreign policy requires strategic recalibration to maintain moral credibility without sacrificing diplomatic efficacy, suggesting a need for greater transparency, public accountability, and explicit alignment with ethical principles. The research contributes to the growing discourse on Islamic ethics in international relations and offers a normative evaluation framework for assessing foreign policy in Muslim-majority democracies.